EFEKTIVITAS MODEL PBL DENGAN PENDEKATAN STEAM UNTUK MENINGKATKAN KEMAMPUAN PEMODELAN MATEMATIS PADA MATERI LISTRIK STATIS - Helsi Hardiana; Stepanus Sahala Sitompul; Hamdani Hamdani (Institut Pendidikan Tapanuli Selatan, 2024)
One of the 21st century skills that must be instilled in students is the ability to solve problems (problem solving), especially in physics learning. In the process of solving physics problems, of course, students will involve mathematical abilities in it. Thus, efforts are needed to train students to be proficient in applying mathematical equations in solving physics problems called mathematical modeling ability (KPM) in physics. Therefore, this study aims to determine the effectiveness of the PBL model with the STEAM approach to improve the mathematical modeling ability (KPM) of students on static electricity material at SMP Negeri 2 Pontianak. This form of research is a pre-experimental design type one-group pretest-posttest design. The research sample was class IX B students at SMP Negeri 2 Pontianak (32 people). Based on the results of the Wilcoxon Test, Asymp values. Sig (2-Tailed) of 0.000 (z< 0.05) this shows that there are differences in the mathematical modeling ability of students in the pretest and posttest, with the level of effectiveness being in the very high category (d = 5.46). Based on response questionnaire data, 97% of students gave a very good response to treatment, and 3% were in the good category. The conclusion of the study is the application of the PBL model with an effective STEAM approach to improve the mathematical modeling ability of students on static electricity material at SMP Negeri 2 Pontianak.